Resonant Faraday effect in a Fabry–Perot cavity - Sycz, Krystian; Gawlik, Wojciech; Zachorowski, Jerzy (Oficyna Wydawnicza Politechniki Wrocławskiej, 2010)
A standard approach to Faraday effect in a Fabry–Perot cavity is extended to resonant absorbing media. The analysis indicates that application of the cavity improves a magnetometric sensitivity despite the resonant absorption. The degree of this improvement depends strongly on the medium’s density and is maximal for diluted media. The best effect is expected with rarified media and/or with weak optical transitions.
Optica Applicata, Vol. 40, 2010, nr 3, s. 633-639
Keywords: optyka; magneto-optical effects; Faraday rotation; optical cavity